2018
DOI: 10.1093/nutrit/nux077
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for improvement of chronic low-grade inflammation in patients with type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials

Abstract: PROSPERO CRD42016047755. Available at: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=47755 (9/15/2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 61 publications
2
54
0
11
Order By: Relevance
“…However, we have previously shown that vitamin D may regulate, rather than suppress, NF‐κB, suggesting a more complex role for vitamin D in immunoregulation than previously described . Nevertheless, the anti‐inflammatory effects of vitamin D in vivo are supported by a recent meta‐analysis by our group of 20 RCTs with >1,200 patients with T2DM, where we showed that vitamin D‐treated groups had lower levels of C‐reactive protein and TNFα than had the placebo group.…”
Section: Vitamin D and Type 2 Diabetessupporting
confidence: 47%
“…However, we have previously shown that vitamin D may regulate, rather than suppress, NF‐κB, suggesting a more complex role for vitamin D in immunoregulation than previously described . Nevertheless, the anti‐inflammatory effects of vitamin D in vivo are supported by a recent meta‐analysis by our group of 20 RCTs with >1,200 patients with T2DM, where we showed that vitamin D‐treated groups had lower levels of C‐reactive protein and TNFα than had the placebo group.…”
Section: Vitamin D and Type 2 Diabetessupporting
confidence: 47%
“…Similar to our findings, vitamin D supplementation lowered inflammatory markers in patients with chronic heart failure (18) . In addition, vitamin D supplementation significantly reduced CRP concentrations in women with gestational diabetes mellitus (37) and patients with T2DM (48) . Moreover, the 8-week flaxseed oil supplementation led to a significant decrease in CRP levels in haemodialysis patients (49) .…”
Section: Effects On Inflammatory Markersmentioning
confidence: 96%
“…It was also shown that T2D subjects with specific genotypes (VDR-Cdx-2AA) respond better to vitamin D supplementation [ 143 ]. A recent meta-analysis of RCTs suggests that vitamin D supplementation improves the chronic low-grade inflammation in T2D patients by reducing the C reactive protein level, TNF-α level, and the erythrocyte sedimentation rate by enhancing the leptin level [ 144 ]. However, in several other studies, no effect of vitamin D supplementation on β-cell function, insulin sensitivity, or glycemic outcomes in pre-diabetic or diet-treated diabetic patients was observed [ 126 , 145 , 146 , 147 , 148 ]…”
Section: Molecular and Clinical Studies Of Vitamin D In Various Dimentioning
confidence: 99%